Postvoiding Urine Accumulation in the Vestibule in a Girl Complaining of Postvoiding Urine Incontinence. Issue 3 (11th October 2013) - SU, Chia‐Cheng; CHANG, Shang‐Jen; YANG, Stephen Shei‐Dei
<x xml:space="preserve">Abstract</x> Postvoiding urine accumulation in the vestibule is clearly demonstrated in a 5‐year‐old girl who suffered from urgent urinary incontinence and postvoiding urine leakage. Before catheterization for urodynamic study, the two labia majorae fused temporarily by sticky mucoid substance and easily separated by the examiner's fingers. Temporary adhesion of labia majora might be the cause of urinary incontinence, which was quickly reversed by correcting to normal voiding posture.